Psychosocial Concerns among Latinas with Life-Limiting Advanced Cancers. (August 2013) - Nedjat-Haiem, Frances R.; Carrion, Iraida V.; Lorenz, Karl A.; Ell, Kathleen; Palinkas, Lawrence
Research has demonstrated that limited dialogue in end-of-life (EOL) care can negatively impact decision-making and place of death. Furthermore, when vulnerable populations are faced with EOL cancer care, they experience issues resulting from previous gaps in services attributed to sociocultural and economic issues that influence EOL care. These conditions place an additional burden on disadvantaged populations which can cause distress, especially as disparate conditions continue to persist. Little is known about Latinos' psychosocial concerns that lead to distress in EOL care. The objective of this study is to explore Latinas' experiences with life-limiting cancer conditions to identify the EOL care concerns that impact their dying experience. This study used a phenomenological approach to explore the EOL care concerns of 24 Latinas receiving treatment for metastatic cancers in a public sector healthcare system in Los Angeles, California. In-depth interviews were recorded and transcribed, and qualitative analysis was performed using Atlas.ti software.